2009
DOI: 10.1055/s-0029-1216374
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 27 Modification is Increased in the Human Diabetic Failing Heart

Abstract: Chronic conditions like diabetes mellitus (DM) leading to altered metabolism might cause cardiac dysfunction. Hyperglycemia plays an important role in the pathogenesis of diabetic complications including accumulation of methylglyoxal (MG), a highly reactive alpha-dicarbonyl metabolite of glucose degradation pathways and increased generation of advanced glycation endproducts (AGEs). The aim of this investigation was to study the extent of the MG-modification argpyrimidine in human diabetic heart and in rat card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
2
24
0
1
Order By: Relevance
“…The crosslink in collagen and elastin increases myocardial stiffness, and impairs its relaxation (Petrova et al 2002;Gawlowski et al 2009). This results in activation of transcription factors, such as nuclear factor-kB (NF-kB) which up-regulates genes that increase the local inflammatory cytokines causing myocardial damage (Burgess et al 2001;Chen et al 2008;Guleria et al 2013;Palomer et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The crosslink in collagen and elastin increases myocardial stiffness, and impairs its relaxation (Petrova et al 2002;Gawlowski et al 2009). This results in activation of transcription factors, such as nuclear factor-kB (NF-kB) which up-regulates genes that increase the local inflammatory cytokines causing myocardial damage (Burgess et al 2001;Chen et al 2008;Guleria et al 2013;Palomer et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The crosslinking involving elastin and collagen results in impaired cardiac relaxation and increased myocardial stiffness. AGEs cause myocardial damage in both humans [22] and animals [23]. …”
Section: Pathophysiological Mechanisms Of Diabetic Cardiomyopathymentioning
confidence: 99%
“…In support, others (24) found that hyperglycemia-induced ROS production in renal cells mediates apoptosis and contributes to diabetic nephropathy. Moreover, diabetic rats display increased expression of genes involved in oxidative stress and apoptosis, e.g., upregulation of Txnip, a negative regulator of the antioxidant thioredoxin and p53 pathway members (15), while H9c2 myoblasts exposed to high glucose levels exhibit decreased expression of heat shock protein 27, resulting in oxidative stress and apoptosis (14). We strengthened our data by including an antioxidant, i.e., 4-OHCA treatment attenuated ROS levels observed under both hyper- C145 glycemic conditions and with PUGNAc treatment (note: 4-OHCA decreases mitochondrial pyruvate uptake and hence attenuates oxidative stress).…”
Section: Hyperglycemia-derived Oxidative Stress Triggers Hbp-mediatedmentioning
confidence: 99%